COVID-19: Recommendations for Optimum Patient Management and Surgeons’ Safety - Bar, Debashish; Alam, ABM Khurshid; Rahman, Fatema; Rahman, AZM Mahfuzur; Suzana, Nawreen (Journal of Bangladesh College of Physicians and Surgeons, 2020)
The novel coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2), has evolved rapidly as a global pandemic stretching the healthcare systems worldwide to their limits. This pandemic has resulted in significant changes to surgical practice across the world. Surgeons need to react immediately to this unexpected clinical challenge in a customized and dynamic approach to the selection, screening, planning, and conduct of surgery for their patients. This current literature will review various international society guidelines to provide a set of recommendations to safely accommodate the exponentially rising cases of SARSCoV- 2 infected patients without compromising the care of emergency surgery and oncological patients or jeopardizing the well-being of hospital staff. The recommendations include guidance for selection and screening of patients during different phases of COVID-19 spread throughout the country. Personal protective equipment requirements for safety measures are also reviewed for each phase as minimum requirements. We also provide recommendations on the patient prioritization for surgery, selection of surgical techniques to reduce transmission and exposure risk, operating room set up and conduct of general surgery. During the COVID-19 pandemic, every surgical unit needs to follow clear guidelines to ensure both patient and staff safety. These current guidelines may assist to provide guidance to units in developing their own protocols. J Bangladesh Coll Phys Surg 2020; 38(0): 116-121